2022
DOI: 10.3934/bioeng.2022013
|View full text |Cite
|
Sign up to set email alerts
|

Fast delivery of melatonin from electrospun blend polyvinyl alcohol and polyethylene oxide (PVA/PEO) fibers

Abstract: <abstract> <p>Water-soluble polymers possess great advantages in current drug delivery systems, such as fast delivery through polymer matrix dissolution as well as promoting solid dispersion of poorly water-soluble drugs. In this work, water-soluble polyvinyl alcohol (PVA) and polyethylene oxide (PEO) were blended (50/50) to electrospin with and without the incorporation of a model drug, melatonin (MLT), at various blend polymer concentrations. Results suggested that increasing blend PVA/PEO soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In contrast, cumulative IBP release gradually increased to 75.5 ± 4.1% and 95.9 ± 0.9% at 1 h and 2 h time points for PCL control fibers, respectively. Studies demonstrated the fast release characteristics of small molecule drugs after incorporation of poloxamer 407 in electrospun hydrophilic fibers, due to the surface wetting and improvement in dissolution of poorly water-soluble drugs [ 14 , 57 ]. In general, poloxamer promoted the wettability of hydrophobic PCL fibers to facilitate the release of small molecule model drugs.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, cumulative IBP release gradually increased to 75.5 ± 4.1% and 95.9 ± 0.9% at 1 h and 2 h time points for PCL control fibers, respectively. Studies demonstrated the fast release characteristics of small molecule drugs after incorporation of poloxamer 407 in electrospun hydrophilic fibers, due to the surface wetting and improvement in dissolution of poorly water-soluble drugs [ 14 , 57 ]. In general, poloxamer promoted the wettability of hydrophobic PCL fibers to facilitate the release of small molecule model drugs.…”
Section: Resultsmentioning
confidence: 99%
“…SEM micrographs were captured from 10 mm working distance, at an accelerating voltage of 15 kV. Using the ImageJ software, the average NF diameter (AD, mean ± SD) was determined, based on at least 50 measurements, from different locations of micrographs [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Electrospinning is a simple, robust, and cost-effective method to produce drug-containing fibers with diameters ranging from tens of nanometers to several micrometers (Chou et al, 2015;Emerine and Chou, 2022). The result is a layer of non-woven fiber mesh that exhibits the texture of typical textiles with a porous structure allowing drainage of the wound exudates and permeation of atmospheric oxygen to the wound (Saghazadeh et al, 2018).…”
Section: Introductionmentioning
confidence: 99%